Diffuse large B-cell lymphoma, multilocalized and extranodal in adult with complete remission: a case report - González, Juan Carlos Trejo; Calderón, Alonso José Molina; Téllez, Abigail Cortés; Rodriguez, Ana Laura Mena; Cárdenas, Luis David González (International Journal of Research in Medical Sciences, 2025)
Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous group of lymphomas. The current classification recognizes an expanding group of distinct entities, with this being the most common. Up to one-third of DLBCL cases may originate in nearly any organ, most commonly in the gastrointestinal tract, skin and soft tissues, bones, or genitourinary tract. A 52-year-old woman with no history of chronic degenerative diseases presented with severe abdominal pain, weight loss, and night sweats. As part of her evaluation, an abdominopelvic CT scan was performed, revealing splenomegaly with internal nodular lesions of undetermined origin, inguinal lymphadenopathy, and cutaneous involvement. A lymphoproliferative process was suggested among the differential diagnoses. Immunohistochemical studies confirmed DLBCL. The patient subsequently received treatment with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone), achieving a cure rate of approximately 50% after six cycles with an adequate response to treatment.